Pengaruh Fasilitas Kerja Unit Aviation Securit Terhadap Kinerja Petugas di Bandar Udara Betoambari Bau-Bau - Dinda Putriani; Kifni Yudianto (Jurnal Bisnis Inovatif dan Digital, 2024)
This study aims to determine and analyze the extent to which work facilities, particularly the X-Ray Cabin, influence the performance of Aviation Security (AVSEC) officers at Betoambari Airport, Baubau. The background of this research is based on field findings indicating that several inspection facilities were either damaged or insufficient, which directly affected the effectiveness of the officers’ work and the smooth operation of the airport. The study uses a quantitative approach with a census method, involving the entire population of 23 AVSEC officers assigned to the X-Ray Cabin area. Data were collected through questionnaires and analyzed using SPSS version 25, employing simple linear regression, t-test, and the coefficient of determination (R²). Indicator analysis also shows that within the work facilities variable (X), the indicator “Ability to Optimize Work Results” received the highest score, indicating the importance of available facilities in supporting daily work efficiency. Conversely, the indicator “In Accordance with Needs” received the lowest score, suggesting that the availability and quality of the X-Ray Cabin are still suboptimal, both in terms of quantity and technical condition. In the performance variable (Y), the indicator “Task Execution” ranked the highest, reflecting the officers’ strong compliance with SOPs and their ability to carry out tasks professionally. However, “Work Quality” was the lowest-scoring indicator, implying that limited facilities directly impact the overall quality of output. The research findings indicate that X-Ray Cabin work facilities have a positive and significant influence on the performance of AVSEC officers, as evidenced by a significance value of 0.000 (< 0.05) and a regression coefficient of 0.926. The coefficient of determination test reveals that the contribution of work facilities to performance reaches 70.2%, while the remaining 29.8% is influenced by other variables outside the scope of this research.